A Century of Partisanship in Finnish Political Speech - Simola, Salla; Nieminen, Jeremias; Tukiainen, Janne (Now Publishers, 2026)
We use novel data to describe the evolution of left–right polarization in parliamentary speech in Finland during 1907–2018. Overall, polarization fluctuates a lot during the majority of the twentieth century. We find the highest peak in left–right polarization in the 1970s. This peak is not explained by the concurrent surge of populism nor by economic conditions, but instead seems driven by Soviet Union related speeches, and especially by the rhetoric of the leftist SKDL party. The peak polarization years in the 1970s are also characterized by inefficient policy-making and higher voter polarization. Although we find polarization has been increasing again since the 1990s to this day, the current levels are low and far from exceptional compared to the 100-year average in overall left–right polarization. However, if we consider polarization without Soviet Union-related speeches, the increasing trend in polarization during the latest decades appears more distinct.